Synthesis, Spectral and Thermal Studies of Praseodymium(III) and Samarium(III) Complexes with N,N?,N?-Tri(2,4- dihydroxybenzophenone)triaminotriethylamine - Thakur, B.G. (Asian Journal of Chemistry, 2010)
A new Schiff base ligand N,N¢,N²-tri(2,4-dihydroxybenzophenone)-triaminotriethylamine (H6L) has been synthesized. Its complexationbehaviour with praseodymium(III) and samarium(III) havebeen observed. The complexes has been characterized by elementalanalysis, IR spectra molar conductivity measurements and thermalanalysis. The praseodymium(III) and samarium(III) cations coordinatewith the tridentate Schiff base nitrogen atoms, the bridgeheadnitrogen atoms and phenolic hydroxyl oxygen atoms.